The influence of mechanochemical modification on prevention of toxic ability of humic acids towards phenanthrene in aquatic environment; IOP Conference Series: Earth and Environmental Science; Vol. 27 : Problems of Geology and Subsurface Development - Shekhovtsova N. S. Natalia Sergeevna; Maltseva E. V.; Glyzina T. S. Tatiana Svyatoslavovna; Ovchinnikova I. S. (Petroleum Engineering Economics. Mining Law, 2015)
Title screen